PENYULUHAN TENTANG KASIAT DAUN SISIK NAGA SEBAGAI PENGOBATAN DIARE DI DESA CANDIREJO - Rika Puspita Sari; Wahyudi Wahyudi (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The purpose of welfare improvement is to strive to further develop the highest welfare status that can really be expected. To achieve this goal, proactive and dynamic administration and regulation are needed that cover all fields, be it government, private or regional. In connection with the above, the creators are interested in leading PKM which intends to provide guidance on giving scale leaves which are believed to be a treatment for diarrhea in Candirejo Village. The reason for holding this PKM is to get a healthy local environment and to avoid diarrheal diseases caused by the living guidance of dragon scale leaves as diarrhea in Candirejo Village. Diarrhea is one of the most well-known infections locally. One of the causes of diarrhea is eating food that is processed ineffective and unhygienic so that the food is contaminated by microbes that are around. If not treated immediately can cause loss of body fluids so that the patient will become dry. Tests saw unusual cases of diarrhea causing death in infants and children. Dragon scale leaves expressly contain a mixture of flavonoids and tannins. These substances are useful as, against pain, death, dry medicine, overcoming ulcers and overcoming bloating. The content of flavonoids and tannins in dragon scales leaves may have an effect. pharmacology for human well-being. It consists of three kinds of stages used in the pemekaran strategy, more specifically: Inviting the local area for PKM training, Input by checking items and things to do, Evaluating the side effects of preparation by estimating the consequences of augmentation preparation. This plant is also efficacious for treating various diseases such as gum disease, stiff neck, bruises, bruises, jaundice, vaginal discharge, breast cancer, mumps, tuberculosis, gonorrhea, gonorrhea and difficult bowel movements. The use of dragon scales leaves as traditional medicine began when a pharmacist found a sick chimpanzee and bit the dragon scales leaves so that the body's condition returned to normal.